Penggunaan Media Simulasi PhET terhadap Hasil Belajar IPA Siswa di SD pada Materi Rangkaian Listrik - Narulita, Lena; Rizqi, Nadia Fathiyatu; Wati, Rahmah; Amelia, Salsabila Dwi; Alpian, Yayan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The PhET simulation media is very helpful for teachers in delivering various physics concepts through interactive simulations. By displaying various phenomena that cannot be directly observed, it can increase students' interest and curiosity. This research focuses on the use of PhET simulation media in Gombong Sari Elementary School. The study uses a qualitative method, with a target of 20 fourth-grade students as subjects. The 20 students conducted simulations using PhET on the topic of electric circuits in science lessons. The data collected was then analyzed, leading to the conclusion that: 1. Using PhET simulations can help teachers easily explain the topic. 2. PhET simulation media has interesting and enjoyable illustrations and can foster higher learning interest. 3. By using PhET simulations, students will be more active and enthusiastic in learning, as PhET provides unique and interesting elements in the teaching and learning process.